2021
DOI: 10.1038/s41598-021-87677-y
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenerational effects in DNA methylation, genotoxicity and reproductive phenotype by chronic arsenic exposure

Abstract: An emerging concern is the influences of early life exposure to environmental toxicants on offspring characteristics in later life. Since recent evidence suggests a transgenerational transference of aberrant phenotypes from exposed-parents to non-exposed offspring related to adult-onset diseases including reproductive phenotype. The transgenerational potential of arsenic a well know genotoxic and epigenetic modifier agent has not been assessed in mammals until now. In this experimental study, we evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 115 publications
0
16
0
3
Order By: Relevance
“…In-utero exposure to sodium arsenite from embryonic day-10 to day-18 at a concentration of 10 ppb induced an increase in leptin levels, and at 42.5 ppm reduced the litter size compared to control mice [137]. Chronic As trioxide exposure to parental male at a dose of 1 mg/L showed genotoxic damage in F0-F3, altered methylation patterns, changes in reproductive parameters, morphological damage in the ovaries (F0 and F1) and testicles (F1-F3), and compromised sperm quality (F0-F3, except F2) [138]. Exposure of sodium arsenite at the dose of 10 mg/L in drinking water to pregnant females from GD1-21 affected body weight and initial sexual development in male pups and relative anogenital distance also showed changes in the expression of SOD1, SOD2, CAT, and GSTK1 gene in male pup rat [139].…”
Section: Pre-natal Arsenic Exposure Induced Male Reproductive Toxicit...mentioning
confidence: 93%
“…In-utero exposure to sodium arsenite from embryonic day-10 to day-18 at a concentration of 10 ppb induced an increase in leptin levels, and at 42.5 ppm reduced the litter size compared to control mice [137]. Chronic As trioxide exposure to parental male at a dose of 1 mg/L showed genotoxic damage in F0-F3, altered methylation patterns, changes in reproductive parameters, morphological damage in the ovaries (F0 and F1) and testicles (F1-F3), and compromised sperm quality (F0-F3, except F2) [138]. Exposure of sodium arsenite at the dose of 10 mg/L in drinking water to pregnant females from GD1-21 affected body weight and initial sexual development in male pups and relative anogenital distance also showed changes in the expression of SOD1, SOD2, CAT, and GSTK1 gene in male pup rat [139].…”
Section: Pre-natal Arsenic Exposure Induced Male Reproductive Toxicit...mentioning
confidence: 93%
“…These results indicate a paternal epigenetic influence on adult F1 and F2 offspring metabolic disease phenotypes. Another study exploring both maternal and paternal exposure on transgenerational health found altered DNA methylation and reproductive phenotypes (Nava‐Rivera et al, 2021). Methylation in the ovary and testes was significantly lower in the F1 generation, remained unchanged in the F2 generation, and increased within the F3 generation.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate a paternal epigenetic influence on adult F1 and F2 offspring metabolic disease phenotypes. Another study exploring both maternal and paternal exposure on transgenerational health found altered DNA methylation and reproductive phenotypes (Nava-Rivera et al 2021). Methylation in the ovary and testes was significantly lower in the F1 generation, remained unchanged in the F2 generation, and increased within the F3 generation.…”
Section: Discussionmentioning
confidence: 99%